Hydrology days award - Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2007)
The 2007 Hydrology Days Award was presented to J-Y Parlange.
Hydrology days 2007
AGU hydrology days 2007
2007 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2007.
Keywords: Hydrology -- Congresses; Award winners